Letter - Stevenson, Daniel M., Sir
042-0134-001 SPA HOTEL, BUXTON, DERBYSHIRE. Proprietors: Buxton Hydropathic Limited. FULLY LICENSED. Telephones 211 and 212 Buxton. Telegrams: "Comfortable," Buxton. July 3rd. 1937. Sir W. Citrine, K.B.E. Transport House, Smith Square, London S.W.1. Dear Sir Walter, Miss Jacobsen sent me from Madrid the enclosed copy of the journal published by the Spanish Medical Sanitary Staff, which she thinks you will find of interest. You will notice that you are mentioned in it. I also enclose a copy of a letter I am sending to various newspapers about the Unit's work, please treat it as private until it appears on the Press. I am, Yours sincerely, D.M. Stevenson Glasgow. 292/946/42/134